2013
DOI: 10.1182/blood-2013-01-478776
|View full text |Cite
|
Sign up to set email alerts
|

Gene-centric association study of acute chest syndrome and painful crisis in sickle cell disease patients

Abstract: Key Points Using genome-wide association study, we found the first replicated genetic association with acute chest syndrome in sickle cell disease patients. The locus identified includes COMMD7, a gene highly expressed in the lung that interacts with NFκB to control inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Because of the high concentration of TPH required to induce it in nonsickle mice, the hemin ALI may be unique to SCD, with in vivo amplification of hemin playing a potentially central role. In addition, free hemin modulates the expression of COMMD7 in cultured pulmonary endothelial cells (50). This gene is highly expressed in the lung (51) and interacts with NF-κB signaling (51,52), and a recent study found that it contains a polymorphism with an array-wide significant association with ACS (P = 4.1 × 10 -7 ) in the Cooperative Study of Sickle Cell Disease cohort (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the high concentration of TPH required to induce it in nonsickle mice, the hemin ALI may be unique to SCD, with in vivo amplification of hemin playing a potentially central role. In addition, free hemin modulates the expression of COMMD7 in cultured pulmonary endothelial cells (50). This gene is highly expressed in the lung (51) and interacts with NF-κB signaling (51,52), and a recent study found that it contains a polymorphism with an array-wide significant association with ACS (P = 4.1 × 10 -7 ) in the Cooperative Study of Sickle Cell Disease cohort (50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, free hemin modulates the expression of COMMD7 in cultured pulmonary endothelial cells (50). This gene is highly expressed in the lung (51) and interacts with NF-κB signaling (51,52), and a recent study found that it contains a polymorphism with an array-wide significant association with ACS (P = 4.1 × 10 -7 ) in the Cooperative Study of Sickle Cell Disease cohort (50). Although more work is needed to clarify the role of the endothelium in our model, these results, together with our present findings using chimeric SS mice, add further evidence in support of a role for hemin signaling in the pulmonary endothelium in ACS.…”
Section: Discussionmentioning
confidence: 99%
“…913 Other clinical risk factors include baseline higher haemoglobin concentration and white blood cell count and lower haemoglobin F concentration. 6 Genetic variation in multiple loci has been associated with the incidence of acute chest syndrome; they include the beta-globin gene cluster haplotype, 14 a (GT)(n) dinucleotide repeat located in the promoter region of HMOX1 (protein HO-1), 15 a single nucleotide roughly 8 kilobases upstream of COMMD7 , 16 and plasma concentrations of HO-1. 17 However, neither laboratory findings nor genetic risk factors are sufficient to stratify children into groups of high or low risk for future acute chest syndrome episodes.…”
Section: Acute Chest Syndrome In Sickle-cell Diseasementioning
confidence: 99%
“…Previous genetic association studies identified that variants at 3 distinct loci ( BCL11A , HBS1L-MYB , and HBB ) are strong determinants of fetal hemoglobin level, and single nucleotide polymorphism (SNP) variant rs6141803 located upstream of COMMD7 is associated with acute chest syndrome. 4 Also, heme-oxygenase-1 gene ( HMOX-1 ) promoter polymorphisms influence heme oxygenase (HO-1) activity and incidence of acute chest syndrome in children with sickle cell disease (SCD). 5,6 We conducted this genome wide association study (GWAS) to identify variants associated with acute severe vaso-occlusive pain in children with SCA enrolled in the Cooperative Study for Sickle Cell Disease (CSSCD) and Silent Infarct Transfusion (SIT) trial.…”
Section: To the Editormentioning
confidence: 99%